The Effect of Think Talk Write Learning Model Containing Science Literacy on Students Learning Competencies In SMA Kartika 1-5 Padang - Annisa Maharani; Syamsurizal Syamsuizal; Rahmawati D; Relsas Yogica (ATRIUM PENDIDIKAN BIOLOGI, 2019)
This research aims to know the positive effect of think talk write model toward students’ learning competencies in grade XI MIPA SMA Kartika 1-5 Padang. The type of this research is quasi experimental with randomized control group posttest only design. Population of this research is all of students grade XI MIPA SMA Kartika 1-5 Padang which is registered in 2018/2019, acounted 158 students from five classes. It’s purposive sampling. The results were selected class XI MIPA 5 as experimental class and class XI MIPA 4 as a control class. The instruments used were in the form of questions posttest for knowledge competency, observation sheets for attitude and skills competency. The hypothesis in this study was tested using the t-test. The results of the study using the t-test it can be concluded that the competency of students' knowledge of the value of tcount 1,82> ttable 1.67, in the competency attitude the value of tcount is 2,30> ttable 1.67, and the competence of value skills tcount 1,80> ttable 1.67. This shows that the hypothesis is accepted. So, it can be concluded that the application of think talk write models with scientific literacy is positively affected toward students’ learning competency in SMA Kartika 1-5 Padang.